Investigation into a GPS time pulse radiator for testing time-stamp accuracy of a radio telescope - Ramudzuli, Zwivhuya Romeo (Department of Electrical Engineering, 2019)
The MeerKAT radio telescope in South Africa is required to tag the arrival time of a signal to within 10 ns of Coordinated Universal Time (UTC). The telescope has a local atomic clock ensemble and uses satellite based remote clock comparison techniques to compare the telescope time to UTC. The master clock timing edge is distributed to each telescope antenna via an optical fibre precise time transfer. Although the timing accuracy of the telescope time was measured internally by the telescope, there is a need for an independent method to verify how well each antenna and its associated processing stages are aligned to UTC. A portable GNSS time-pulse radiator (GTR) device for testing the time-stamp accuracy was developed. The GTR was calibrated at the National Metrology Institute of South Africa and laboratory characterisation tests measured its RF timing pulse to be 1.32 ± 0.100 µs ahead of the UTC second. The telescope’s time and frequency reference clock ensemble consists of two hydrogen masers, an ultrastable crystal and GPS disciplined Rubidium clocks. During operation, the GTR radiates a broadband GPS time synchronised RF timing signal at a known distance from the telescope antennas and the corresponding timestamps were compared to the expected value. Recent GTR timing tests performed on one of the MeerKAT antennas showed that the telescope’s generated timestamps associated with the GTR’s RF timing signal coincided with the expected delay of approximately 16 ± 0.1 µs measured from an antenna 4.8 km away from the telescope’s master clock transmitter. Ultimately we used the GTR to verify that the telescope time and UTC were aligned to within 100 ns. Future work is planned to improve the profile of the transmitted signal and timing critical hardware in order to reduce the GTR’s error budget.